Two new Species of Neischnocolus Petrunkevitch, 1925 (Araneae: Theraphosidae) from Eastern and Western Ecuador - Peñaherrera-R., Pedro; Guerrero-Campoverde, Ariel; León-E., Roberto J.; Pinos-Sánchez, Andrés; Falcón-Reibán, José M. (Zootaxa, 2023)
Two new species of Neischnocolus Petrunkevitch, 1925 are described from the eastern and western slopes of the Andean Cordillera of Ecuador. N. tsere sp. nov. differs from all congeners by having the prolateral inferior keel well developed and longer than prolateral superior keel, prolateral inferior and prolateral superior keels slightly serrated at distal section, prolateral inferior keel not continuous, and retrolateral keel absent. N. cisnerosi sp. nov. differs from all congeners by having a prolateral accessory keel, retrolateral keel, prolateral superior and prolateral inferior keels non-serrated, and the presence of median dorsal granular area rounded-shaped over ventral surface. Comments on biogeography of Neischnocolus are made.